GIG ECONOMY: ECONOMIC BENEFITS AND SOCIAL RISKS - Ashrafova Nozima A'zamovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This research provides an extensive academic inquiry into the "Gig Economy" as a transformative structural shift in the global labor market. It examines the proliferation of platform-mediated work, highlighting the transition from traditional long-term employment to decentralized, task-based labor. The article provides a detailed evaluation of economic advantages, such as enhanced market agility and entrepreneurial freedom, while simultaneously investigating the profound social risks, including the erosion of the social safety net and the precariousness of algorithmic management. The study emphasizes the necessity of developing "portable benefits" and updated legal classifications to ensure a sustainable future for digital labor.